63.1k views
1 vote
H(x)= (x^2 -36)/x +6 explain why the following function is not continuous at x=-6

User Makky
by
4.7k points

1 Answer

1 vote

You can solve this problem through factoring.

First, you have the equation,


h(x) = (x^2-36)/(x-6)

Then, you can factor the numerator.


h(x) = ((x+6)(x-6))/(x-6)

You can cancel out the x-6 in both the numerator and the denominator because they would equal to just 1.

You are left with
h(x) = x+6

The function is removable noncontinuous at x=6 because if you plug in 6 in x-6, your denominator would be undefined.

User Victor Gazotti
by
5.5k points